Pengembangan Wisata Religi Banten Lama - Riza Subban Alhakimi; Weishaguna (UNISBA Press, 2022)
Abstract. The issue which states that there are indications that Banten Lama religious tourism cannot develop from now on because stakeholders have not made efforts to develop religious tourism and have not paid more attention to its development. Then find out the problem. The problem covers two aspects, namely aspects of tourist attraction and aspects of management and service. Based on the above background, the formulation of the problem arises, whether religious tourism in Banten Lama can be more developed. With the aim of knowing whether or not the Old Banten religious tourism could be more developed. The analysis used in this research is descriptive analysis of the scale range. The analyzed aspect is the aspect of tourist attraction with the factors assessed are, tourist attraction, accessibility, tourism support facilities, tourism support services, conditions around the area and accommodation. Aspects of management and service with assessed factors are management and service, organizational structure, master plan, “Collaborative Management” of cross-sectoral agencies and Sapta Pesona. Answering from the problem formulation that says whether Banten Lama religious tourism can be more developed. Based on the results of the analysis and discussion in the previous chapter, it was concluded that the Old Banten religious tourism